Financial Control as a Means of Cognition of the Financal Activities: Theoretical and Legal Aspects - CHERNADCHUK, Viktor D.; CHERNADCHUK, Тamara O.; KLOCHKO, Alyona M. (Journal of Advanced Research in Law and Economics, 2018)
The article deals with the actual issues of the financial control from the point of view not only as a type of activity, management function or institution of the financial law, but also as a means of knowledge of the financial activity. The result of such cognition is an establishment of the actual state of affairs in the sphere of the financial activity by comparing them (comparisons) and assessing their compliance with the normative model of financial activity, in terms of legality and efficiency, detecting deviations from this model (violations of the financial legislation) and other negative trends, and as well as developing and taking measures to bring actual financial activity to its normative model. The global experience of financial control organization confirms the need to reorganize the existing system of state financial control in Ukraine and determines the need to create an organizational structure for establishing a system of external and internal financial control at the appropriate methodological and regulatory basis. One of the prerequisites for improvement of financial legislation is the cognition not only the results of the financial activity, but also the conditions, factors and circumstances the presence of which contributes to a violation of financial legislation, the causes of these violations, etc. The results of control measures, despite the selectivity of controlled entities and the limited range of these entities, are part of that initial empirical material, which requires cognition, which can result in a generalized conclusion on the state of financial activity as a whole. The article proposes the author's vision of the directions of further improvement of financial legislation of Ukraine and the influence on the development of this branch of legislation of the results of financial control.